Romania - Functional Review : Romania Competition Council - World Bank (Washington, DC, 2013)
The European Union is founded on a competitive market economy unified by commonly agreed rules and practices. While Romania has joined the Union, its ability to prosper fully within the common market requires a strengthened commitment to, and ability to protect, EU competition principles. Romania's legal and organizational framework for enhancing competition is tenuous and the current economic and fiscal crisis puts recent gains at risk. In particular, Romania's performance in competition policy still lags behind EU practice and is characterized by: (i) State-owned enterprises and government participation still play a dominant role in many important markets and sectors in Romania, controlling at least one firm in 14 key sectors of the economy and exhibiting a market share above 50% in at least one segment of network industries. (ii) Relatively low enforcement of competition policy against hard-core cartels and abusive practices while merger review cases that do not significantly impose threats to competition account for the bulk of the workload in the competition area. (iii) Low staffing for competition enforcement and economic analysis placing the Romania Competition Council (RCC) at the bottom of European Union rankings with no internal target deadlines to track performance. (iv) Active advocacy activities mainly focus on raising awareness of the importance of competition law but efforts need to be made to refocus activity on tackling anticompetitive regulation, expand advocacy to key groups within the government and implement alternative advocacy tools. A comprehensive reform program therefore is required at the national level, as well as within the Romanian Competition Council (RCC) as the key agency in guaranteeing healthy competition. Priority actions, further detailed in this report, include the following: (i) improve the competitive environment by reducing the dominant role of the state in several economic sectors, (ii) provide space for a redoubled RCC focus on competition enforcement establish a new unit within RCC to target hard core anti-competitive behavior take immediate steps, within the principles of the government's unified pay system, to ensure a level of compensation to core RCC competition staff commensurate with their responsibilities in front of the judiciary and private sector.